Quantitative assessment of distance to collection point and improved sorting information on source separation of household waste. (June 2015) - Rousta, Kamran; Bolton, Kim; Lundin, Magnus; Dahlén, Lisa
Highlights: The effects of interventions in a source separation system were quantified. Decreased distance to drop-off point resulted in improved sorting of recyclables (28%). Proper information in a convenient system decreased the miss-sorted fraction (70%). Property close collection system accepting several waste fractions was more effective. Abstract: The present study measures the participation of households in a source separation scheme and, in particular, if the household's application of the scheme improved after two interventions: (a) shorter distance to the drop-off point and (b) easy access to correct sorting information. The effect of these interventions was quantified and, as far as possible, isolated from other factors that can influence the recycling behaviour. The study was based on households located in an urban residential area in Sweden, where waste composition studies were performed before and after the interventions by manual sorting (pick analysis). Statistical analyses of the results indicated a significant decrease (28%) of packaging and newsprint in the residual waste after establishing a property close collection system (intervention (a)), as well as significant decrease (70%) of the miss-sorted fraction in bags intended for food waste after new information stickers were introduced (intervention (b)). Providing a property close collection system to collect more waste fractions as well as finding new communication channels for information about sorting can be used as tools to increase the source separation ratio. This contribution also highlights the need to evaluate the effects of different types of information and communication concerning sorting instructions in a property close collection system.